NUMBUHKAN TAAT HUKUM SEBAGAI IMPLEMENTASI HUKUM DI INDONESIA BERDASAR ATAS HUKUM - Dody Wahono Suryo Alam (Sekolah Tinggi Ilmu Syariah Abu Zairi Bondowoso, 2024)
The level of legal awareness and citizens' adherence to the law can show the progress of a country. This factor of legal awareness and legal consciousness has an important role in the development of law; in other words, the lower the legal awareness of the community, the less legal compliance; conversely, the higher the legal awareness of the community, the stronger the legal compliance. The life of society and the state as a whole is more orderly. The research method uses descriptive qualitative. Research findings, public legal awareness which in turn will create a good law enforcement atmosphere, which can provide a sense of justice, create legal certainty in society and provide benefits for community members. The way to increase legal obedience or awareness is through education, enforcement and the role of society. With education means teaching that every human being is strived to have legal awareness of how to be a good citizen, the community will know about actions that violate the rules. In addition, law enforcement and the role of the community also need to be carried out in monitoring citizens' obedience to the law so that all people strive to obey.